Level of Knowledge on Tooth Brushing, Diet, and Dental Health Control among Students at Sekolah Alam Cikeas - Zakiyyah Zahra; Ika Ratna Maulani; Agus Ardinansyah (YARSI Dental Scientific Meeting - e Journal, 2025)
Background: Dental and oral health is an important part of general health that plays a role in supporting quality of life. Low levels of knowledge about dental and oral health care are still one of the causes of high rates of dental caries among school-age children in Indonesia. Objective: This study aims to determine and compare the level of knowledge about dental and oral health among elementary school, junior high school, and senior high school students at Sekolah Alam Cikeas (SAC). Methods: This study used a quantitative descriptive research design with a cross-sectional approach using a questionnaire instrument. The study sample consisted of 60 students, comprising 20 elementary students, 20  junior high school students, and 20  senior high school students of Sekolah Alam Cikeas. The questionnaire contained 30 questions covering three aspects, namely knowledge about brushing teeth, diet, and dental health check-ups at the dentist. Data analysis was performed descriptively by grouping knowledge categories into good, moderate, and poor. Results: The results showed that the majority of students at all levels of education had a good level of knowledge. Knowledge about brushing teeth showed a good percentage of 90% among elementary school students and 100% among junior high and high school students. Knowledge about diet was in the good category with a percentage of 90% among elementary and junior high school students and 95% among high school students. Knowledge about dental health control showed variation, namely 70% in the good category among elementary school students, 65% among junior high school students, and 90% among high school students. Conclusion: There is a tendency for an increase in the level of dental and oral health knowledge along with increasing levels of education. Knowledge about dental health control still needs to be improved, especially among elementary and junior high school students.